MULTIDISCIPLINARY REHABILITATION SYSTEM FOR CHILDREN WITH SEVERE DEVELOPMENTAL DISORDERS (International journal of artificial intelligence, 2025)
Children with severe developmental disorders face complex challenges that require coordinated efforts from various specialists to optimize their functional abilities and quality of life. This article examines the importance of a multidisciplinary rehabilitation system designed to address the diverse physical, cognitive, emotional, and social needs of these children. The integration of medical, educational, psychological, and social interventions within a unified framework ensures comprehensive support. The article highlights contemporary approaches, the roles of different specialists, and the impact of early and continuous rehabilitation efforts.